2013
DOI: 10.1002/acp.2959
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Bias in Verbal Credibility Assessment: Criteria‐Based Content Analysis, Reality Monitoring and Scientific Content Analysis

Abstract: Verbal credibility assessment encompasses several methods used to evaluate the credibility of statements by examining their content. In two experiments, we tested to what extent these methods are sensitive to contextual bias. Four statements were presented, although their context was manipulated by confronting raters with extra-domain information that either enhanced or diminished the credibility of the statements. In Experiment 1, 32 police officers analysed the statements using scientific content analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…But what do such field studies look like? Research has shown that prior information about the guilt of a suspect-for example, about a confession-influences the outcomes of subsequent forensic tests, including the outcomes of lie detection tests (e.g., Bogaard, Meijer, Vrij, Broers, & Merckelbach, 2014;Elaad, Ginton, & Ben-Shakhar, 1994;Kassin, Dror, & Kukucka, 2013). Given the large number of degrees of freedom, especially when it comes to interpreting fMRI data, analysis of deception detection results may be prone to biasing observer effects.…”
Section: Legal Implicationsmentioning
confidence: 99%
“…But what do such field studies look like? Research has shown that prior information about the guilt of a suspect-for example, about a confession-influences the outcomes of subsequent forensic tests, including the outcomes of lie detection tests (e.g., Bogaard, Meijer, Vrij, Broers, & Merckelbach, 2014;Elaad, Ginton, & Ben-Shakhar, 1994;Kassin, Dror, & Kukucka, 2013). Given the large number of degrees of freedom, especially when it comes to interpreting fMRI data, analysis of deception detection results may be prone to biasing observer effects.…”
Section: Legal Implicationsmentioning
confidence: 99%
“…Another example of a cognitive bias was provided by Bogaard et al (2014). They showed that ratings of RM criteria were affected by extra-domain information, so that statements which were accompanied by positive information (e.g., a positive eye-witness identification) were judged as being richer in RM criteria than statements which were accompanied by negative information (e.g., a personal background that implied a history of lying).…”
Section: Cognitive Biasesmentioning
confidence: 99%
“…A list of 12 criteria is mostly used in workshops on the technique (Driscoll, 1994), in research (Smith, 2001), or by SCAN users in a field observation (Bogaard, Meijer, Vrij, Broers, & Merckelbach, 2014). SCAN is popular in the field and probably is frequently, and widely used.…”
mentioning
confidence: 99%
“…Despite its widespread use, no research has supported claims of SCAN's diagnostic accuracy and several studies showed that the SCAN criteria could not differentiate between true and fabricated accounts [Bogaard, Meijer, & Vrij, 2014 (see Chapter 6); Bogaard et al, 2014a (see Chapter 5); Nahari et al, 2012;Vanderhallen et al, 2015]. In a previous study, we investigated whether -in absence of diagnostic accuracy -susceptibility to confirmation bias could serve as an alternative explanation for SCAN's popularity (see Chapter 2; Bogaard et al, 2014a). In the current study, we extend this line of research by including SCAN criteria to investigate whether SCAN's popularity could be explained by the intuitive plausibility of its items.…”
Section: Introductionmentioning
confidence: 93%
“…CBCA was originally developed for evaluating children's testimonies in cases of alleged sexual abuse, but several studies have shown that CBCA can also be used for adults, and is not restricted to sexual abuse cases (Akehurst, Köhnken, & Höfer, 2001;Sporer, 1997;Vrij et al, 2002Vrij et al, , 2004a. Both field studies (Lamb et al, 1997;Raskin & Esplin, 1991;Roma et al, 2011) and lab studies Bogaard, Meijer, Vrij, Broers, & Merckelbach, 2014a;Vrij et al, 2002Vrij et al, , 2004b reported that CBCA is able to accurately discriminate between truthful and fabricated statements. Several meta-analytic reviews, and one meta-analysis have shown that the average accuracy rate of CBCA varies around 70% (Amado et al, 2015;Amado et al, 2016;Oberlader et al, 2016;Vrij, 2005).…”
Section: Introductionmentioning
confidence: 99%